Significance of Assessing Vocabulary in the Classroom - Eshonkulova Nasiba Khasanovna (Peerian Journals Publishing, 2022)
This article discusses several ways of evaluating students’ vocabulary progress in the classroom while learning foreign languages. Measuring vocabulary is also one of the main points in learning and teaching foreign languages, as well as evaluating language skills like reading, listening, writing and speaking.
Keywords: assessment; multiple choice; quizzes; synonyms and antonyms comprehension